Human herpesvirus 6 and multiple sclerosis: survey of anti-HHV-6 antibodies by immunofluorescence analysis and of viral sequences by polymerase chain reaction. Issue 8 (August 1993) - Sola, P; Merelli, E; Marasca, R; Poggi, M; Luppi, M; Montorsi, M; Torelli, G
Abstract : A possible involvement of human herpesvirus 6 (HHV-6) infection in the pathogenesis of multiple sclerosis (MS) was investigated. The immunofluorescence analysis of sera from 126 MS patients showed significantly higher anti-HHV-6 antibody titres in MS sera than in 500 normal controls. A polymerase chain reaction (PCR) assay of the peripheral blood mononuclear cell (PBMC) DNAs of 31 MS patients and 24 normal subjects was positive in one normal control and in one MS patient. The Southern blot analysis indicated an unexpectedly high level of viral sequences in the MS patient, but not in the control. Since viral sequences are rarely present in MS subjects, the high anti-HHV-6 antibody titres found in MS are likely to be related to immune impairment rather than reactivation of a latent infection.